2010
DOI: 10.1097/mpg.0b013e3181c1f5b3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying Time of Oral Contrast Material in Children and Adolescents Undergoing Abdominal Computed Tomography

Abstract: : Given the variability of GET of OCM and if clinically feasible, we advocate waiting at least 3 hours between completion of OCM ingestion and general anesthesia induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Also, the risk of aspiration after administration of oral contrast media should be taken into account. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of aspiration after administration of oral contrast media should be taken into account. 11 …”
Section: Discussionmentioning
confidence: 99%
“…In 1 particular study, 50% of patients were reported to have residual oral contrast in the stomach for greater than 1 hour after administration; 25% of patients were found to have residual oral contrast in the stomach for greater than 2 hours, and a single patient was found to have oral contrast in the stomach nearly 3 hours after administration. 5 In light of these findings, the authors advocated waiting at least 3 hours between the administration of oral contrast for CT and the induction of general anesthesia, introducing the potential for delays in management. In a recent large study analyzing the effects of oral contrast, it was found that in nearly 20% of patients with appendicitis, the administration of oral contrast material induced emesis, and nasogastric tubes were place in more than 5% of patients for the administration of oral contrast.…”
Section: Oral Contrastmentioning
confidence: 98%
“…The administration of enteric contrast medium in children who require sedation/anesthesia for abdominal computed tomography (CT) has been a long-standing practice at most large pediatric centers [ 4 ]. While a 2010 study of 101 children found that 75% of patients had enteric contrast medium in the stomach 48 ± 5.2 min after the completion of enteric contrast medium ingestion, 50% after 74 ± 7.9 min, and 25% after 135 ± 32.5 min [ 5 ], the current goal is to obtain a CT scan within one hour of receiving enteric contrast medium [ 6 ] because, in 83% of cases, small bowel transit time is less than two hours. While the average small bowel transit time is one hour and 24 min, transit time can be as fast as 15 min [ 7 ].…”
Section: Introductionmentioning
confidence: 99%